PENGARUH METODE LATIHAN DAN MOTIVASI BERLATIH TERHADAP KETERAMPILAN PUKULAN ATLET WUSHU KATEGORI SANSHO - Nurtia Nilam Sari (JURNAL PENDIDIKAN ROKANIA, 2017)
This study aims to see the influence of guided discovery style exercise methods, self-examination style exercise methods, and motivation to practice on wushu athlete skills. Type of research used is quasi experiment. The population of this research is wushu athletes solok count 90 people. The sample group was taken by purposive sampling. Instrument motivation practice is measured by using questionnaires and blow skills using a punch skills test consisting of Straight and Hook blows. The data obtained were then analyzed by two-way analysis of variance (ANAVA) and continued with the Tukey test. From the data analysis of the research results obtained: (1) there is a significant difference between athletes trained by using the practice of guided discovery style have a significant effect on the skill of wushu athlete of Sanshoudari category on using self-examination practice method. (2) There is an interaction between blow skill and the motivation to practice on improving skill of wushu athlete of sanshou category. (3) In high motivation practice, guided invention style practice method gives big influence from self-examination style method to improving skill of wushu athlete Sanshou category. (4) On the motivation of low practice, there is no significant difference of influence between the method of practicing self-examination style with the method of practicing guided discovery style to the improvement of skill of wushu athlete of Sanshou category